Natural latex films as carrier for casearia sylvestris swartz extract associated with ciprofloxacin - Bolognesi, Luis Felipe Cesar [UNESP]; Borges, Felipe Azevedo [UNESP]; Cinman, José Luiz Ferreira [UNESP]; Silva, Rosângela Gonçalves da [UNESP]; Santos, André Gonzaga dos [UNESP]; Herculano, Rondinelli Donizetti [UNESP] (Sciencedomain International, 2015)
In order to create a new sustained drug delivery system applied for tissue regeneration, this study beget a natural rubber latex (NRL) film with Casearia sylvestris extract and ciprofloxacin. Manipulated from the biomaterial latex obtained by the rubber tree Hevea brasiliensis, the NRL film has shown to be a great angiogenic compound and also has shown a great potential in being a possible carrier for sustained drug release. In order to increase the therapeutic spectrum of the film two substances was added to it: the C. sylvestris extract which has antiulcer, anti-inflammatory and wound healing effects due to its casearins and the antibiotic ciprofloxacin which is considered as one of the main drugs used for open wounds in the skin. The study occurred at State São Paulo University in Assis (UNESP-FCL), Brazil. The substances were mixed and a film was made by casting at ambient temperature creating circular films with 5cm of diameter. After that the film was placed in 1 liter of water to start the release study. The release behavior was analyzed by UV-VIS spectrophotometry being the casearins related to the wavelength of 235nm and the ciprofloxacin of 320nm. The film supported the release of compounds, releasing 93.73% of the extract and 56.53% of the drug, along 29 hours. In addition, the incorporation was proven by Scanning Electron Microscopy (SEM), which showed the morphology of pure and incorporated films and also by Fourier Transform Infrared Spectroscopy (FTIR) which has shown that no chemical change occurred during the process. Thereby, according to results, the material has a possible approach to biomedical application.
Keywords: Sustained release; Latex; Casearia sylvestris; Ciprofloxacin; Biomaterials; Casearia sylvestris Swartz; Ciprofloxacin; Natural rubber